Effectiveness of elite female basketball players' technical-tactic actions and ways for their improvement at stage of maximal realization of individual potentials - R.A. Sushko; E.Y. Doroshenko (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose: study effectiveness of elite female basketball players' technical-tactic actions and determine the ways for their improvement at stage of maximal realization of individual potentials. Material: the authors analyzed competition functioning's indicators of female basketball players of national combined team of Ukraine and their age characteristics. Results: effectiveness of technical-tactic actions in structure of national female basketball players' combined team of Ukraine competition functioning at European championship. The authors present: indicators of team composition; roles in team; won and lost games; quantity of scored and skipped points; technical-tactic actions; age of sportswomen. Age indicators of elite female basketball players at stage of maximal realization have been given. Conclusions: we have composed a list of the most important technical-tactic actions in competition functioning. We also outlined ways for their perfection at stage of maximal realization of individual potentials of elite female basketball players of different game roles.